Targeted chromosomal cleavage and mutagenesis in Drosophila using zinc-finger nucleases. - Bibikova, Marina (2002)
Zinc-finger nucleases (ZFNs) are hybrids between a nonspecific DNA-cleavage domain and a DNA-binding domain composed of Cys(2)His(2) zinc fingers. Because zinc fingers can be manipulated to recognize a broad range of sequences, these enzymes have the potential to direct cleavage to arbitrarily chosen targets. We have tested this idea by designing a pair of ZFNs that recognize a unique site in the yellow (y) gene of Drosophila. When these nucleases were expressed in developing larvae, they led to somatic mutations specifically in the y gene. These somatic mosaics were observed in approximately one-half of the males expressing both nucleases. Germline y mutations were recovered from 5.7% of males, but from none of the females, tested. DNA sequences were determined and showed that all of the mutations were small deletions and/or insertions located precisely at the designed target. These are exactly the types of alterations expected from nonhomologous end joining (NHEJ) following double-strand cleavage of the target. This approach promises to permit generation of directed mutations in many types of cells and organisms.